DOES QUALITY COST? - Bouillon, Adolfo (2020)
Zero defects production is a goal that every company pursue; failing that objective returns poor results on the long term. Inventory management, business forecasting and quality management help to achieve profitability objectives. Forecasting models must be analysed in detail in order to make better production decisions. Quality management seeks foster a long-term culture in organizations. Studies show that long term benefits of quality management widely outperform its short-term costs.